Skills in Solving Mathematical Problems in the Statistics Subject Using Interactive Multimedia in Grade VI of Elementary School - Kusumaningpuri, Aditya Rini; Murtiyasa, Budi; Fuadi, Djalal; R, Laili Etika; Fauziati, Endang (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Problem-solving skills are one that students shall have in learning mathematics. To assist students in developing problem-solving skills, Information and Communication Technology (ICT) may be used, one of which is interactive multimedia. Therefore, this research aims to use interactive multimedia to describe students' mathematical problem-solving skills in statistics at the elementary school level. This research uses descriptive qualitative research with a case study model. Research subjects aged 11-12 years in collecting data, the researcher used an instrument for performance indicators and then strengthened interviews (unstructured) with educators and students. Then analyzed using an In this study, researchers used the theory of Miles and Huberman. Overall, the analysis of students' problem-solving skills is already very skilled. It has been proven that almost all students achieve performance indicators, namely, capable of understanding the problems presented, carrying out solution planning, solving problems according to plan indicators, and conducting re-examinations to re-examine them.  This research implies that teachers can apply interactive multimedia to increase student activity in learning.